2022
DOI: 10.7759/cureus.22841
|View full text |Cite
|
Sign up to set email alerts
|

Blunt Cardiac Injury in Patients With Sternal Fractures

Abstract: BackgroundBlunt cardiac injury (BCI) is a possible consequence of sternal fractures (SF). There is a scarcity of studies addressing BCI in patients with different types of SF and with pre-existing cardiac conditions. The goal of this study was to delineate diagnostic patterns of BCI in different cohorts of SF patients. MethodsThis retrospective cohort study included 380 blunt trauma patients admitted to two level 1 trauma centers between January 2015 and March 2020 with radiologically confirmed SF. Electrocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The rate of death in the current research was 16.3% (25 cases). Our findings were comparable to those of Fokin et al (32) who reported a death rate of 16% in their BCI patients. This was in accordance with the findings of Keskpaik et al (22) who demonstrated that the total in-hospital death rate was 17.0 percent (25/147).…”
Section: Resultssupporting
confidence: 92%
“…The rate of death in the current research was 16.3% (25 cases). Our findings were comparable to those of Fokin et al (32) who reported a death rate of 16% in their BCI patients. This was in accordance with the findings of Keskpaik et al (22) who demonstrated that the total in-hospital death rate was 17.0 percent (25/147).…”
Section: Resultssupporting
confidence: 92%
“…The depth of sternal displacement is considered a sign of an increased risk of injury to adjacent structures such as the heart and lungs [ 18 ]. Similar to that reported in other studies, this study shows that 28 (44.4%) patients had some degree of sternal fracture displacement [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no statistically significant differences were observed in sternal fracture displacement between patients with multiple injuries and those with an isolated sternal fracture. The displaced sternal fractures are considered theoretically more dangerous, although previous studies have shown no statistically significant association between displaced fractures and the severity of blunt cardiac injuries or associated lung injuries [ 9 , 18 ]. Similar to the results reported in a previous study, sternal fractures occur most frequently in the body of the sternum, and no fractures have yet reported the involvement of the xiphisternum [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sternal fractures were strongly associated with blunt cardiac injury. Previous studies reported sternal fractures in approximately 2% of blunt trauma cases [ 33 , 34 ], while in 2.4–8% of patients with sternal fractures, blunt cardiac injury were also observed [ 33 , 35 , 36 , 37 ]. Observational studies in the United States and Germany using large databases have also reported that sternal fracture is associated with blunt cardiac injury [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%